Dopagem substitucional de peroviskitas com metais de transição 3d: um estudo ab initio - Chagas, Lucas Guilherme (Universidade Federal de São Carlos, 2022)
The global demand for energy has brought into focus the halide perovskites as materials with high potential for applications in photovoltaic devices. Great progress has been made in the last 10 years, demonstrating the possibility of surpassing the efficiency of current silicon-based technology with the advantage of lower costs and ease of synthesis. However, there are two drawbacks for its large-scale commercial use: (i) the most efficient perovskites currently have lead in their composition, generating strong toxicity; (ii) in addition, there is structural instability, resulting in degradation, and consequent loss of its properties. This degradation can lead to the release of lead, and is greater in the case of perovskites with organic cations. As an alternative, perovskites with inorganic cations, such as Cs + , have been explored. It is also common to replace lead with non-toxic metallic cations, such as Sn 2+ . In particular, CsSnI3 is a promising lead-free perovskite for applications in photovoltaic devices. However, this material has two phases at room temperature: Black (photo-active) and Yellow (photo-inactive), the second being more stable, but without potential for applications in photovoltaic devices due to its wide bandgap (2,4 eV ). In this work, we study the substitutional doping of CsSnI 3 with transition metals 3d at the site of Sn through simulations ab initio based on density functional theory. The dopants are Sc , Ti , V , Cr , Mn , Fe , Co , Ni , Cu , and Zn . The study was divided into three stages: (i) study of CsSnI3 without defects; (ii) doping 100% to understand the limits of high concentration; (iii) partial doping in concentration of 12,5%. The results of step (i) indicate that the Yellow phase is more stable than the Black phase, and that local structural distortions are essential to obtain a bandgap in agreement with experimental data. Step (ii) indicated that dopants in high concentrations can improve the stability of CsSnI3 . Step (iii) shows that there is a reduction of the lattice parameter for dopings with Sc , V , Cr and Mn . However, some dopants induce Jahn-Teller distortions in octahedra, namely, Co , Ni , Cu and Zn . The calculation of the energy of formation shows that the doping with Sc is exothermic, while the others are endothermic. Most defects have the most stable neutral state of charge. The only exceptions are doping with Ni and Cu . Furthermore, the dopants V , Cr , Fe and Co introduce states into the bandgap. Finally, our most relevant result was the inversion of the most stable phase for dopants with a greater number of electrons 3d. That is, the black phase is more stable when we doped CsSnI3 with Co , Ni , Cu , and Zn . Our work demonstrated that the stability of perovskites can be controlled with substitutional doping, and indicated the main effects of this doping on the structural and electronic properties of CsSnI3.
Substitutional doping of perovskites with 3d transition metals: an ab initio study
Keywords: Peroviskita; CsSnI3; Dopagem substitucional no sítio B; DFT; Peroviskite; Doping substitutional in site B; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESTRUTURA ELETRONICA DE ATOMOS E MOLECULAS; TEORIA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::ESTADOS ELETRONICOS